Selectivity of (±)-citalopram at nicotinic acetylcholine receptors and different inhibitory mechanisms between habenular α3β4* and α9α10 subtypes. (December 2019) - Arias, Hugo R.; Jin, Xiao-Tao; Gallino, Sofía; Peng, Can; Feuerbach, Dominik; García-Colunga, Jesús; Elgoyhen, Ana Belén; Drenan, Ryan M.; Ortells, Marcelo O.
Abstract: The inhibitory activity of (±)-citalopram on human (h) α3β4, α4β2, and α7 nicotinic acetylcholine receptors (AChRs) was determined by Ca 2+ influx assays, whereas its effect on rat α9α10 and mouse habenular α3β4* AChRs by electrophysiological recordings. The Ca 2+ influx results clearly establish that (±)-citalopram inhibits (IC50 's in μM) hα3β4 AChRs (5.1 ± 1.3) with higher potency than that for hα7 (18.8 ± 1.1) and hα4β2 (19.1 ± 4.2) AChRs. This is in agreement with the [ 3 H]imipramine competition binding results indicating that (±)-citalopram binds to imipramine sites at desensitized hα3β4 with >2-fold higher affinity than that for hα4β2. The electrophysiological, molecular docking, and in silico mutation results indicate that (±)-citalopram competitively inhibits rα9α10 AChRs (7.5 ± 0.9) in a voltage-independent manner by interacting mainly with orthosteric sites, whereas it inhibits a homogeneous population of α3β4* AChRs at MHb (VI) neurons (7.6 ± 1.0) in a voltage-dependent manner by interacting mainly with a luminal site located in the middle of the ion channel, overlapping the imipramine site, which suggests an ion channel blocking mechanism. In conclusion, (±)-citalopram inhibits α3β4 and α9α10 AChRs with higher potency compared to other AChRs but by different mechanisms. (±)-Citalopram also inhibits habenular α3β4*AChRs, supporting the notion that these receptors are important endogenous targets related to their anti-addictive activities. Highlights: (±)-Citalopram inhibits hα3β4 with higher potency than that for hα7 and hα4β2 AChRs. (±)-Citalopram inhibits α9α10 AChRs in a voltage-independent manner. (±)-Citalopram inhibits habenular α3β4* AChRs in a voltage-dependent manner. Radioligand binding and molecular docking (MD) support a luminal location at α3β4. MD differentiates competitive (α9α10) vs noncompetitive (α3β4) inhibitory mechanisms.